Native American whalemen and the world : the contingency of race - Shoemaker, Nancy, 1958- (The University of North Carolina Press, 2015)
In the 19th century, nearly all Native American men living along the southern New England coast made their living travelling the world's oceans on whaleships. Many were career whalemen, spending 20 years or more at sea. Exploring the shifting racial ideologies that shaped their lives, Nancy Shoemaker shows how the category of 'Indian' was as fluid as the whalemen were mobile.